Cognitive frailty: a useful concept or a source of confusion? Insights from a survey of European geriatricians - Suzanne Timmons; Mary Faherty; Catriona Curtin; Maria Cristina Ferrara; Giuseppe Bellelli; Enrico Brunetti; Mario Bo; Alessandro Morandi; Antonio Cherubini; Massimiliano Fedecostante; Alessandra Coin; Susan D. Shenkin; et al. (BMC Geriatrics)
Abstract Background This report examines how European geriatricians understand the concept of ‘cognitive frailty’, which was first formally defined by the International Academy on Nutrition and Aging (IANA) and the International Association of Gerontology and Geriatrics (IAGG) in 2013. Methods An online survey about delirium, dementia and frailty relationships and pathways was distributed across Europe through appropriate professional groups. Eligible participants were geriatricians or trainees in their final two years of specialist geriatric training, in a European country. Snowball sampling was used. In total, 440 people replied to the survey, of which 324 responded to the section on cognitive frailty. Respondents were predominantly female and there was a marked under-representation of Eastern European participants. Results From a list of possible definitions, only one in four of the 324 respondents identified cognitive frailty as defined by the IANA and the IAGG, i.e., a combination of physical frailty and mild cognitive impairment. Almost two thirds of those who stated that they currently use the term in their work did not choose the IANA-IAGG definition. After the definition was shared with respondents, only 44% strongly agreed with it as an apt description of cognitive frailty, with some considering it too narrow (by omitting delirium and dementia) while others considered it too broad (by including physical frailty). Conclusions There is no clear consensus opinion among geriatricians in Europe on the definition of ‘cognitive frailty’. While there is some core support for the IANA-IAGG definition, it is not intuitive to those not already familiar with the term. The variance in the current understanding of cognitive frailty among geriatricians suggests the time is right for a meaningful debate on this issue. While there is ongoing, growing research on a shared pathophysiology between physical frailty and cognitive impairment, further studies are required to evaluate the added benefit of this particular conceptual theorization in older persons care rather than its single components, and if beneficial, how awareness, understanding and correct usage of the concept can be improved.